Nerve Regeneration Restores Supraspinal Control of Bladder Function after Complete Spinal Cord Injury - Lee, Yu-Shang (Society for Neuroscience, 2013)
A life-threatening disability after complete spinal cord injury is urinary dysfunction, which is attributable to lack of regeneration of supraspinal pathways that control the bladder. Although numerous strategies have been proposed that can promote the regrowth of severed axons in the adult CNS, at present, the approaches by which this can be accomplished after complete cord transection are quite limited. In the present study, we modified a classic peripheral nerve grafting technique with the use of chondroitinase to facilitate the regeneration of axons across and beyond an extensive thoracic spinal cord transection lesion in adult rats. The novel combination treatment allows for remarkably lengthy regeneration of certain subtypes of brainstem and propriospinal axons across the injury site and is followed by markedly improved urinary function. Our studies provide evidence that an enhanced nerve grafting strategy represents a potential regenerative treatment after severe spinal cord injury.